Combination of cadonilimab (PD-1/CTLA-4 bispecific antibody) and apatinib as salvage therapy achieves partial response in MSI-H advanced gastric cancer: a case report - Zhao, Jiayu; Li, Xiaoxiao; Sun, Xiaoyuan; Xiao, Ruoxi; Xue, Juan; Sui, Kexin; Liu, Zimin (Frontiers in Immunology, 2025)
Microsatellite instability-high (MSI-H) gastric cancer (GC) is recognized as a unique subtype of gastric cancer. While patients with advanced MSI-H gastric cancer may respond favorably to a combination of immune checkpoint inhibitors and chemotherapy in first-line treatment, no definitive recommendations exist regarding the optimal regimen for subsequent therapy. Cadonilimab, a PD-1 and CTLA-4 bispecific antibody, has shown encouraging efficacy and safety in the first-line treatment of advanced gastric cancer. However, its utility in the MSI-H gastric cancer subtype following multiple lines of therapy remains uncertain. This case report describes a patient with advanced MSI-H gastric adenocarcinoma that progressed after multiple treatments and achieved notable efficacy with a combination of cadonilimab and apatinib. By examining the current therapeutic landscape for MSI-H gastric cancer, this study explores the potential of combining PD-1/CTLA-4 dual-immunity with anti-vascular therapy as salvage treatment for this gastric cancer subtype. The findings provide valuable reference points for future clinical trials, offering a promising perspective on backline therapeutic strategies for MSI-H gastric cancer and highlighting the potential of integrating bispecific antibodies with anti-vascular therapies.